engaruh Metode Bermain Peran Terhadap Percaya Diri Siswa Sekolah Dasar - Anggy Giri Prawiyogi; Haerudin; Andri Purwanugraha; Mega Agustin (LPPM Universitas Buana Perjungan Karawang, 2019)
This study aims to determine the effect of student’s of Cengkong IV Elementary School Purwasari Distric. This research is a type of quantitative research. The population used in this student were all students of Cengkong IV Elementary School with a total of 150. By taking a sample of 25% of the population members, a sample of 40 people was obtained. The technique of collecting data through student confidence questionnaires with student’s speaking skills using the role playing method. Data analysis techniques to test hypotheses are done by calculating inferensial statistics. The results of the test of the validity of the confidence questionnaire obtained 22 items of instrument statements which were validly stated from the 46 statments of the instruments being tested.